Mechanisms of immune regulation by the placenta: Role of type I interferon and interferon‐stimulated genes signaling during pregnancy - Ding, Jiahui; Maxwell, Anthony; Adzibolosu, Nicholas; Hu, Anna; You, Yuan; Liao, Aihua; Mor, Gil (Immunological reviews, 2022)
Pregnancy is a unique condition where the maternal immune system is continuously adapting in response to the stages of fetal development and signals from the environment. The placenta is a key mediator of the fetal/maternal interaction by providing signals that regulate the function of the maternal immune system as well as provides protective mechanisms to prevent the exposure of the fetus to dangerous signals. Bacterial and/or viral infection during pregnancy induce a unique immunological response by the placenta, and type I interferon is one of the crucial signaling pathways in the trophoblast cells. Basal expression of type I interferon‐β and downstream ISGs harbors physiological functions to maintain the homeostasis of pregnancy, more importantly, provides the placenta with the adequate awareness to respond to infections. The disruption of type I interferon signaling in the placenta will lead to pregnancy complications and can compromise fetal development. In this review, we focus the important role of placenta‐derived type I interferon and its downstream ISGs in the regulation of maternal immune homeostasis and protection against viral infection. These studies are helping us to better understand placental immunological functions and provide a new perspective for developing better approaches to protect mother and fetus during infections.